Greek banking from the pre-euro reforms to the financial crisis and beyond - Pasiouras, Fotios (Palgrave Macmillan studies in banking and financial institutions, 2012)
From a period of growth and considerably high levels of profitability, Greek banks recently found themselves battling a major decrease in demand in the local market, and an increase in non-performing loans. How is the Greek banking system able to survive the crisis? This is discussed by looking at the last 15 years of the Greek banking system.